A Case of Syphilitic Uveitis in Which Vitreous Surgery Was Useful for the Diagnosis and Treatment - Kobayashi, Takatoshi (Case Rep Ophthalmol, 2017)
PURPOSE: To report a case of atypical syphilitic uveitis complicated with retinal vasculitis, proliferative retinopathy, and vitreous hemorrhage in which vitreous surgery was useful for the diagnosis and treatment. CASE REPORT: A 38-year-old female was referred to our hospital after noticing visual disturbance in her right eye. Fundoscopy examination of that eye revealed retinal phlebitis accompanied by retinal hemorrhage and soft exudate, and remarkable exudative changes in the retinal vessels from the upper arcade to the macula region. After a blood examination, a serological test showed positive for syphilis; however, systemic findings were scarce. Syphilitic uveitis was suspected, so we administered treatment for syphilis, anticoagulant treatment for retinal vasculitis, steroids for intraocular inflammation, and photocoagulation for the retinal nonperfusion area. However, her visual acuity (VA) decreased to 30 cm/counting fingers due to vitreous hemorrhage resulting from fibrovascular membrane at the optic disc. Since the vitreous hemorrhage was insufficiently absorbed, vitreous surgery was performed to remove the hemorrhage and fibrovascular tissue. Following surgery, the uveitis and retinal vasculitis subsided, and her corrected VA improved to 0.3. Postoperative examination of a fixed quantity of collected vitreous fluid for syphilis showed a Treponema pallidum hemagglutination value of 5,120 times the normal amount, thus confirming the syphilitic uveitis diagnosis. CONCLUSIONS: Our findings show that when observing patients with obstructive retinal vasculitis of unknown causes, syphilitic uveitis should be considered as a differential diagnosis, and that vitreous surgery is useful for the diagnosis and treatment of atypical syphilitic uveitis which has progressed to proliferative retinopathy.